BENEFITS OF INTERNATIONAL PORTFOLIO DIVERSIFICATION FOR THE INDIAN INVESTOR - Singh, Nikhil (2008)
This dissertation provides evidence to support the hypothesis that suggests that there are long-term benefits for the Indian investors to diversify in the international equity markets. The evidence is based on the data from the stock markets of India and ten other international markets, over the period from 1st January 1998 to 31st December 2007. The methodology adopted was to construct a correlation coefficient matrix in order to examine the correlations between the Indian stock market and other international markets. In order to identify the markets for investment purposes, the mean, the standard deviation and the Sharpe's ratio was also calculated for each index of the selected markets. It was found that there was very low correlation between the Indian and the international markets. None of the chosen markets influenced the Indian markets significantly, and there were markets which offered higher returns suggesting that there are benefits available to investors who want to diversify in international markets. Therefore, the conclusion was that, there may still be benefits from diversifying across international equity markets. This result may be valuable information for Indian investors who would like to take advantage of the international diversification strategy while constructing their portfolios.